The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1242/dev.02795
|View full text |Cite
|
Sign up to set email alerts
|

Fxna, a novel gene differentially expressed in the rat ovary at the time of folliculogenesis, is required for normal ovarian histogenesis

Abstract: In rodents, the formation of ovarian follicles occurs after birth. In recent years, several factors required for follicular assembly and the growth of the newly formed follicles have been identified. We now describe a novel gene, Fxna, identified by differential display in the neonatal rat ovary. Fxna encodes an mRNA of 5.4 kb, and a protein of 898 amino acids. Fxna is a transmembrane metallopeptidase from family M28, localized to the endoplasmic reticulum. In the ovary, Fxna mRNA is expressed in granulosa cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…The protein product of this gene, in a rat, is required for the organization of somatic cells and oocytes into discrete follicular structures. No ERMP1 mutations have been reported in humans [20]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein product of this gene, in a rat, is required for the organization of somatic cells and oocytes into discrete follicular structures. No ERMP1 mutations have been reported in humans [20]. …”
Section: Discussionmentioning
confidence: 99%
“…By differential display in the neonatal rat ovary, Garcia-Rudaz et al [20] identified a novel cDNA, termed fxna (felix-ina), expressed during folliculogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the specific function and substrate-specificity of Pff1 has yet to be elucidated, a whole genomic analysis of proteins that respond to the absence of the PFF1 ( YBR074w ) gene product is consistent with the protein playing a role in vacuolar function. Interestingly, a putative mammalian homolog of Pff1 exists 141 . However, the mammalian protein was instead found to reside in the ER and appears to be involved in ovarian development.…”
Section: The Vacuolar Proteasesmentioning
confidence: 99%
“…We have employed gain-of-function approaches to define the involvement of astroglial cells (Ma et al, 1994;Prevot et al, 2003;Rage et al, 1997;Sandau et al, 2009) and specific neuronal subsets (Bilger et al, 2001;Heger et al, 2003) in the hypothalamic control of puberty, and loss-of-function strategies to identify three upstream transcriptional regulators of the pubertal process (Heger et al, 2007;Mastronardi et al, 2006;Ojeda et al, 1999), and four subordinate genes involved in neuron-neuron communication (Choi et al, 2008;Garcia-Rudaz et al, 2008;Ha et al, 2008;Sandau et al, 2009). Because lentiviruses (Tiscornia et al, 2003) can efficiently deliver small interfering (si)RNAs to tissues or cells of interest (Garcia-Rudaz et al, 2007;Heger et al, 2007), we have used this delivery system to determine if decreasing the production of EAP1 would alter the onset of female puberty and adult reproductive cyclicity (Heger et al, 2007). We observed that Eap1 siRNA-producing lentiviral particles injected bilaterally into the preoptic area (POA) of juvenile 23-day-old rats results in delayed puberty, disrupted estrous cyclicity, reduced plasma LH, FSH and estradiol levels, and delayed growth of ovarian follicles.…”
Section: Genes Controlling Puberty Are Organized In Functional Netmentioning
confidence: 99%